Measure the overall economic rate of return for university education for selected colleges in Iraq - Ibrahim, Husna Nasir; Al-Kabisi, Muhamad Salah (Journal of University of Human Development, 2015)
The research aims to estimate the rate of economic return year on higher education in the College of Business and Economics - University of Baghdad as part of the public sector and Baghdad College of Economic Sciences University within the private sector and the use of function Minsr, through polled a sample of staffing the kidneys, study sample included the first for 52 personnel and members of the second sample 50 individuals. resolution has been used as a tool head to collect data and information of samples Alambhuthtin, and achieve the goals of the research used a number of statistical tools after confirmation of sincerity and persistence, and research has reached into the most important results, but the 1.Estimated economic rate of return year for university education in the College of Business and Economics - University of Baghdad with 14% at the level of industry as a whole for the year 2011 which means that the economic rate of return for the year educational achieve an increase in the income of an educated person about 14%, while the estimated economic rate of return of general education at Baghdad College of Science Economic University about 9%: that achieves greater rate of return for the educational year in the tertiary education sector private sector as a whole level of 9% for the year 2011 2. Consequent weak positive relationship between experience and return as the percentage increase revenue derived from the limitation of 2% in both sectors public and private education.